Two‐week test–retest reliability of the Polar® RS800CX™ to record heart rate variability. (27th January 2016) - Williams, DeWayne P.; Jarczok, Marc N.; Ellis, Robert J.; Hillecke, Thomas K.; Thayer, Julian F.; Koenig, Julian
Summary: Recently, research has validated the use of Polar ® heart rate monitors as a tool to index heart rate variability (HRV). In the current investigation, we sought to evaluate the test–retest reliability of both time and frequency domain measures of HRV using the Polar ® RS800CX ™ . Continuous HRV data were collected as 60 nominally healthy adults underwent a resting and orthostatic stress test. We evaluated reproducibility by means of the interclass correlation coefficient for absolute agreement and consistency, and the standard error of measurement. We found moderate reliable 2‐week test–retest reliability of HRV using the Polar ® RS800CX ™, results that are in line with previous studies that have validated the stability of HRV using other methods of measurement (e.g. electrocardiogram). Additionally, when examining different methods of spectral density estimation, we found that using the auto‐regressive transformation method provides the most stable indices of HRV. Taken together, our results suggest that the Polar ® RS800CX ™ is not only a valid method to record HRV, but also a reliable one, particularly when using the auto‐regressive transformation method.